The concept of qudwah hasanah and Muslim women's roles in the strengthening of the ummah: an analysis of recent Malay novels - Kamarudin, Kamariah (Dewan Bahasa dan Pustaka, 2013)
In the contex of Islam, the concept of qudwah hasanah, that is, a good example or model, is not only applicable to men but also to women in society. Qudwah hasanah is important, for one, because it helps to strengthen the family institution, and the ummah as a whole. In line with this, women are equally responsible for realizing qudwah hasanah, especially since women are considered to be “educators” by nature. In many works of Malay literature in this country, Muslim women are presented as the central figures around which these works revolve. A great number of female characters in these works are shown to have exemplary characteristics. Because of this, the present study aims to examine the characteristics of qudwah hasanah in relation to the female characters in several recent Malay novels published by women authors, namely Baromkeh Matamu di Mataku (Baromkeh: Seeing Through Your Eyes) by Ummu Hani Abu Hassan, Seteguh Fikrah Saleha (As Strong as Saleha’s Thought) by Aminah Mokhtar, Delima Ranting Senja (The Pomegranate of the Evening Branch) by Siti Zainon Ismail, Episod Cinta di Tanah Hijrah (Love in the Land of Migration) by Amaruszati Noor Rahim, and Lentera Mustika (Mustika’s Lantern) by Nisah Haron. This study also examines the extent to which local women authors are able to create female Muslim characters in line with the concept of qudwah hasanah.